Respuesta :
Answer:
The standard form is [tex]=29+11i[/tex]
Step-by-step explanation:
We need to write the provided expression in standard form
Given expression is [tex](7-5i)(2+3i)[/tex]
first simplified the [tex](7-5i)(2+3i)[/tex]
[tex]\mathrm{Apply\:complex\:arithmetic\:rule}:\quad \left(a+bi\right)\left(c+di\right)=\left(ac-bd\right)+\left(ad+bc\right)i[/tex]
[tex]a=7,\:b=-5,\:c=2,\:d=3[/tex]
[tex]=\left(7\cdot \:2-\left(-5\right)\cdot \:3\right)+\left(7\cdot \:3+\left(-5\right)\cdot \:2\right)i[/tex]
further simplify
[tex]=29+11i[/tex]
Therefore, the standard form is [tex]=29+11i[/tex]